Examining sensory differences of children with autism in early childhood: Effects of school and home settings - Girli, Alev (Journal of Human Sciences, 2016)
Recently, towards stimuli giving over sensitive or insensitive reactions has been recognized as diagnostic distinctive characteristics in children with autism. One of the purposes of this study is to determine behaviors which behaviors are result of sensitivity, prevalence rate at home or school settings and types of occurrence seen by parents and teachers. Another purpose of this study is to examine parent and teacher views on sensitivity effects at school and home settings. Study group consist 22 children with autism (2-6 ages), 20 mothers, and 8 trainers (4 psychologists and 4 special education teachers) who work with those children. In order to collect types of sensitivity and prevalence rate, “Sensory Difference Observation Form” and in order to collect views of parents and teachers, a semi structured form, “Effects of Sensory Differences: Parent and Teacher Views Form” are used. Forms were designed by researcher. It has been determined that the insensitivity of children towards movement, touch as well as auditory, visual and taste-scent stimuli is more common with a higher ratio than sensitivity. It has been observed that these properties have negative effects on their home lives as well as the routines of families and that teachers cope with them more easily in school settings.